ANALISIS PENGENDALIAN KUALITAS SEBAGAI STRATEGI KEBERLANJUTAN USAHA DENGAN METODE SEVEN TOOLS PADA PT. SIDOKUMPUL RAYA - Mariza Ayu Putri Lestari; Suaibatul Aslamiyah (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the application of Quality Control using the Seven Tools of Quality as a strategy to support business sustainability in 8.0 mm diameter wire mesh products at PT Sidokumpul Raya, with a focus on identifying the dominant types of defects, the factors causing defects, and production process improvement efforts that can be undertaken by the company. This study uses a descriptive qualitative approach with the research location at PT Sidokumpul Raya, Gresik Regency. Data collection was carried out through direct observation of the production process, in-depth interviews with four informants who understood Quality Control in the company in accordance with the criteria, as well as documentation of production data and product defect data. Data analysis was performed by applying the Seven Tools of Quality, which include histograms, Pareto diagrams, cause-and-effect diagrams (Fishbone diagrams), control charts (P-Charts), and scatter diagrams. The results of the study show that the dominant defects in 8.0 mm diameter wire mesh products include size non-compliance with SNI standards, product inaccuracy, and suboptimal welded joints. The main causes of defects originate from aspects of machinery, production processes, operator skills, and the environment. The use of the Seven Tools for Quality Control plays a role in business sustainability, including resource and raw material savings, and even customer satisfaction. This study is limited to one type of product, namely 8.0 mm diameter wire mesh, and focuses on internal Quality Control within the company without discussing marketing and distribution aspects. The implications of this study indicate that the systematic application of Quality Control through the Seven Tools of Quality can serve as a basis for evaluating and improving production processes to reduce defect rates, increase operational efficiency, and support the sustainability of the company's business.